Dirāsah Tahlīliyah Liltadribāt Fī Kitāb Ta’lim Allughah Al’arabiah Lilshafi Al Awwal Almutawasiṯ Liwizārah Alsyu`ūn Aldīniyah Al Indūnisiyah ām 2020 - Ahmad Fahmi Hidayat; Arif Taufiqurrahman (Mauriduna: Journal of Islamic Studies, 2022)
This study aims to know the analysis of the exercises in the Arabic language teaching book for the first intermediate class of the Indonesian Religious Ministry in 2020, and this research is expected to help teachers to know the standards of good exercises, and as a reference source in knowing the training models in the Arabic language teaching book for the first intermediate class of the Religious Ministry indonesian 2020, It is expected that this research will help teachers to know the standards of good exercises, and as a reference source in knowing the training models in the Arabic language teaching book for the first intermediate class of the Indonesian Religious Ministry in 2020, in order to visualize the teacher in forming appropriate teaching strategies with the book’s training materials. This study relies on the analytical descriptive method, by looking at the exercises in the "Book of Teaching Arabic for the First Intermediate Class of the Indonesian Religious Ministry in 2020", and the conclusion thereof. The conclusion from this study is that the exercises in the book included all types of exercises, and that in the exercises of the book there were some notes and several advantages. Penelitian ini bertujuan untuk mengetahui analisis soal latihan dalam buku ajar bahasa arab kelas menengah pertama Kementerian Agama RI Tahun 2020, dan penelitian ini diharapkan dapat membantu guru untuk mengetahui standar latihan yang baik, dan sebagai sumber referensi dalam mengetahui model-model latihan dalam buku ajar bahasa arab kelas menengah pertama Kementerian Agama indonesia tahun 2020, penelitian ini diharapkan dapat membantu guru untuk mengetahui standar-standar latihan yang baik, dan sebagai sumber referensi dalam mengetahui model-model latihan. dalam buku ajar bahasa arab kelas menengah pertama Kementerian Agama RI tahun 2020, untuk memvisualisasikan guru dalam membentuk strategi pengajaran yang sesuai dengan materi pelatihan buku. Penelitian ini menggunakan metode deskriptif analitis, dengan melihat soal-soal latihan dalam “Kitab Pengajaran Bahasa Arab Kelas Menengah Pertama Kementerian Agama Indonesia Tahun 2020”, dan kesimpulannya. Kesimpulan dari penelitian ini adalah bahwa latihan dalam buku ini mencakup semua jenis latihan, dan dalam latihan buku terdapat beberapa catatan dan beberapa kelebihan.